Exploring the adaptability of TeachABI as an online professional development module for high school educators - Christine F. Provvidenza; Hiba Al-Hakeem; Elizabeth Ramirez; Rick Rusyn; Shauna Kingsnorth; Sara Marshall; Kylie Mallory; Shannon E. Scratch (Elsevier, 2024)
Objective: Educators often lack the knowledge and resources to assist students with acquired brain injury (ABI). TeachABI, an education module, was created to help elementary school teachers support students with ABI in classrooms. This study examined the adaptability of TeachABI for high school educators. Methods: A qualitative descriptive study explored high school educators' (n = 9) experiences reviewing TeachABI and its adaptability for high school through semi-structured interviews. The interview guide was informed by implementation and adaptation frameworks. Transcripts were examined using directed content analysis. Results: Teachers felt TeachABI was a good foundation for creating a high school-based education module. Adaptations were highlighted, such as streamlining content (e.g., mental health) and strategies (e.g., supporting test taking), to better meet educator needs. Conclusions: Using implementation science and adaptation frameworks provided a structured approach to explore the adaptive elements of TeachABI. The module was perceived as a suitable platform for teaching high school educators about ABI. Innovation: TeachABI is an innovative, user informed education module, providing a multi-modal (e.g., case study, videos) and replicable approach to learning about ABI. Applying frameworks from different fields provides concepts to consider when tailoring resources to align with educator needs (e.g., grade, class environment) and facilitate innovation uptake.